2018
DOI: 10.1002/jso.24999
|View full text |Cite
|
Sign up to set email alerts
|

Is BMI associated with post‐operative complication risk among patients undergoing major abdominal surgery for cancer? A systematic review

Abstract: We systematically reviewed 118 studies comparing peri-operative outcomes among obese and non-obese patients. Obesity was associated with longer operative time in 60% of available studies. Just 35.8% of studies that evaluated overall morbidity identified high morbidity in obese patients. Lymph node yield or surgical margin status, was only affected by obesity in 19.6% of studies. In this review obesity was frequently found to have no effect on peri-operative and oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 130 publications
(621 reference statements)
0
14
0
Order By: Relevance
“…Patients with extremely high BMI have more subcutaneous fat and thicker fat layer. Obesity may adversely affect surgical outcomes in patients after major abdominal surgery owing to limited field of view, operation difficulties during surgeries and co-morbidities ( 4 , 38 ). Obese patients may also be exposed to inadequate lymph node dissection and increased intraoperative complications ( 4 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with extremely high BMI have more subcutaneous fat and thicker fat layer. Obesity may adversely affect surgical outcomes in patients after major abdominal surgery owing to limited field of view, operation difficulties during surgeries and co-morbidities ( 4 , 38 ). Obese patients may also be exposed to inadequate lymph node dissection and increased intraoperative complications ( 4 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obese patients often show higher rates of mortality and morbidity after RC compared to those of normal BMI, likely due to increased perioperative blood loss and prolonged operative times for overweight individuals [24]. Pulmonary compromise due to the Trendelenburg position and abdominal pressure on the diaphragm may also lead to an increased risk of pneumonia, heart failure, deep venous thrombosis, and pulmonary embolism in these patients [25]. Such patients may also be at increased risk of infections and impaired wound closure after RC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al recently reported a signi cant difference in the overall complication incidence of obese patients and nonobese patients after major abdominal surgery in gastric, rectal and liver cancers [5]. Apart from increasing di culties during cytoreductive surgery, obesity may also contribute to more postoperative complications and higher costs [6].…”
Section: Introductionmentioning
confidence: 99%